Cross-sectional survey of knowledge of obstetric danger signs among women in rural Madagascar - Ania Salem; Oriane Lacour; Stefano Scaringella; Josea Herinianasolo; Anne Caroline Benski; Giovanna Stancanelli; Pierre Vassilakos; Patrick Petignat; Nicole Christine Schmidt (BMC, 2018)
Abstract Background Antenatal care (ANC) has the potential to identify and manage obstetric complications, educate women about risks during pregnancy and promote skilled birth attendance during childbirth. The aim of this study was to assess women's knowledge of obstetric danger signs and factors associated with this knowledge in Ambanja, Madagascar. It also sought to evaluate whether the participation in a mobile health (mHealth) project that aimed to provide comprehensive ANC to pregnant women in remote areas influenced women's knowledge of obstetric danger signs. Methods From April to October 2015, a non-random, convenience sample of 372 women in their first year postpartum were recruited, including 161 who had participated in the mHealth project. Data were analyzed using bivariate and multivariate logistic regression. Results Knowledge of at least one danger sign varied from 80.9% of women knowing danger sign(s) in pregnancy, to 51.9%, 50.8% and 53.2% at delivery, postpartum and in the newborn, respectively. Participation in the mHealth intervention, higher household income, and receipt of information about danger signs during pregnancy were associated with knowledge of danger signs during delivery, in bivariate analysis; only higher household income and mHealth project participation were independently associated. Higher educational attainment and receipt of information about danger signs in antenatal care were associated with significantly higher odds of knowing danger sign(s) for the newborn in both bivariate and multivariate analysis. Conclusions Knowledge of obstetric danger signs is low. Information provision during pregnancy and with mHealth is promising. Trial registration This trial was retrospectively registered at the International Standard Randomized Controlled Trial Register (identifier ISRCTN15798183; August 22, 2015).